2021
DOI: 10.28991/cej-2021-03091760
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pressure Distribution on an Irregular Octagonal Plan Oval-Shape Building Using CFD

Abstract: This paper aims to study the wind flow characteristics and to analyze the wind pressure distribution on the surfaces around an irregular octagonal plan shape building model. There is a central open space in plan to provide more surface area around the building for natural ventilation. Plan area of the building is 300 m2(excluding the open space) and height is 50 m. Steady state flow of wind with 5% turbulence (moderate turbulence) under atmospheric boundary layer has been taken in the study. Numerical simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…In truth, CFD is a method of numerically solving these equations and obtaining flow variables as a result. The number of unknown variables, such as velocity, pressure, and temperature must be defined for each flow field variable [30,31]. Even for more difficult flows such as turbulent and free surface motion flows, a unique numerical solution may be demonstrated theoretically in the majority of cases.…”
Section: Methodsmentioning
confidence: 99%
“…In truth, CFD is a method of numerically solving these equations and obtaining flow variables as a result. The number of unknown variables, such as velocity, pressure, and temperature must be defined for each flow field variable [30,31]. Even for more difficult flows such as turbulent and free surface motion flows, a unique numerical solution may be demonstrated theoretically in the majority of cases.…”
Section: Methodsmentioning
confidence: 99%
“…[1] calculated the uncertainties that arise while using computational fluid dynamics to forecast wind loads for full-scale constructions. [2] analyzed the properties of wind flow and the distribution of wind pressure on the surfaces of an octagonal-shaped building model. [3] studied the effects of wind on tall buildings using CFD simulation in various ways.…”
Section: Introductionmentioning
confidence: 99%
“…Raj et al (2020) [24] numerically investigate wind action on "H" plan shaped tall buildings. Kumar and Raj (2021) [25] numerically investigated the pressure distribution on an irregular octagonal plan oval shape building model and a detailed analysis of wind effects is provided in the form of pressure contours. [26] evaluated the interference effect on corner configured structures with variable geometry and blockage configurations under wind loads using CFD and it is observed that shielding effect suppress the interference effects on the principal building.…”
Section: Introductionmentioning
confidence: 99%